Gilbert B. Colfield, Laws, Ordinances and Rules of Nebraska City 36 (1872) - (:unkn) unknown (My University, 1873)
Ordinance No. 7, An Ordinance Prohibiting the Carrying of Fire Arms and Concealed Weapons, § 1: That it shall be, and it is hereby declared to be unlawful for any person to carry, openly or concealed, any musket, rifle, shot gun, pistol, sabre, sword, bowie knife, dirk, sword cane, billy slung shot, brass or other metallic knuckles, or any other dangerous or deadly weapons, within the corporate limits of Nebraska City
Keywords: CARRY